A Cross‐linguistic Examination of Toddlers' Interpretation of Vowel Duration. (13th January 2019) - Swingley, Daniel; van der Feest, Suzanne V. H.
Abstract : Languages differ in their phonological use of vowel duration. For the child, learning how duration contributes to lexical contrast is complicated because segmental duration is implicated in many different linguistic distinctions. Using a language‐guided looking task, we measured English and Dutch 21‐month‐olds' recognition of familiar words with normal or manipulated vowel durations. Dutch but not English learners were affected by duration changes, even though distributions of short and long vowels in both languages are similar, and English uses vowel duration as a cue to (for example) consonant coda voicing. Additionally, we found that word recognition in Dutch toddlers was affected by shortening but not lengthening of vowels, matching an asymmetry also found in Dutch adults. Considering the subtlety of the cross‐linguistic difference in the input, and the complexity of duration as a phonetic feature, our results suggest a strong capacity for phonetic analysis in children before their second birthday.